Public Service Delivery: Role of Information and Communication Technology in Improving Governance and Development Impact - Subhash Bhatnagar (Asian Development Bank (ADB), 2014)
The focus of this paper is on improving governance through the use of information and communication technology (ICT) in the delivery of services to the poor, i.e., improving efficiency, accountability, and transparency, and reducing bribery. A number of papers recognize the potential benefits but they also point out that it has not been easy to harness this potential. This paper presents an analysis of effective case studies from developing countries where the benefits have reached a large number of poor citizens. It also identifies the critical success factors for wide-scale deployment. The paper includes cases on the use of ICTs in the management of delivery of public services in health, education, and provision of subsidized food. Cases on electronic delivery of government services, such as providing certificates and licenses to rural populations, which in turn provide entitlements to the poor for subsidized food, fertilizer, and health services are also included. ICT-enabled provision of information to enhance rural income is also covered.
hdl:11540/4206
Keywords: D73; H11; O30; O57; 330; e-governance; ICT for development; service delivery; anticorruption; transparency; process reform